Perceptions of educators and students about using fluoridated mouthwashes - Martins, Ronald Jefferson [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Garbin, Artênio José Isper [UNESP]; Shimada, Dirce Sato; Castilho, Augusto Pereira de (My University, 2010)
Purpose: The objective of this study was to assess the perceptions and opinions of public school teachers and students in the city of Araçatuba, SP, Brazil, on the importance of using fluoridated mouthwashes, the difficulties of the method and the procedure in general. Methods: Students from grades 5 through 8 in schools with and without dental services were asked about their opinion on the use of fluoridated mouthwashes. The educators answered questions about the importance of preventive methods in oral health and the difficulties in performing those methods at school. Data were collected using a faces scale, a categorization method, and a Likert scale with five levels of responses to check the level of agreement with the questions. Results: The sample consisted of 264 (40.3%) teachers and 5,788 (73.6%) students. A total of 254 (96.2%) and 72 (27.3%) teachers responded favorably to the first and second questions, respectively. A total of 1,128 (19.5%) students had negative feelings about the fluoridated mouthwash. Conclusion: The majority of the teachers supported the use of fluoridated mouthwashes; however, a large number of teachers believed that the practice disrupts the class routine. Most of the students had a positive opinion about the use of fluoridated mouthwash, although they highlighted some negative aspects, which were overcome by the benefits that the method provides.

Objetivo: O objetivo deste trabalho foi avaliar a percepção de educadores e alunos das escolas públicas de Araçatuba, SP, Brasil, sobre a importância da prática, dificuldades e sentimentos em relação aos bochechos fluorados. Metodologia: Selecionaram-se as escolas sem e com atenção de saúde bucal por cirurgiãodentista. Os alunos de 5ª a 8ª séries responderam perguntas sobre o sentimento em relação ao bochecho. Utilizou-se a escala de faces de Andrews, que é uma escala intervalar de sete pontos composta por faces estilizadas e a metodologia da temática simples para análise das questões. Os educadores responderam a perguntas sobre a importância do método preventivo e dificuldades na sua realização. Utilizou-se a Escala de Likert com o formato típico de cinco níveis de respostas para verificar o nível de concordância com as perguntas. Resultados: A amostra consistiu de 264 (40,3%) educadores e 5.788 (73,6%) alunos, que responderam o questionário. Do total, 254 (96,2%) dos educadores responderam favoravelmente à primeira questão e 72 (27,3%), à segunda questão. Um total de 1.128 (19,5%) alunos mostrou sentimento negativo em relação ao bochecho. Conclusão: A maioria dos educadores foi favorável à realização dos bochechos, entretanto grande parte acredita atrapalhar o bom andamento da escola. A maior parte dos alunos apresentou um sentimento positivo em relação ao bochecho, inclusive relevando aspectos considerados ruins pela percepção do benefício que o método proporciona.
Percepção de educadores e alunos sobre a realização de bochechos fluorados
Keywords: Dental caries; Primary prevention; Sodium fluoride; Cárie dentária; Prevenção primária; Fluoreto de sódio